1990
DOI: 10.1111/j.1755-3768.1990.tb01897.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of the light reflex of retinal vessels to reduced blood pressure in hypertensive patients

Abstract: The response of retinal arteries and veins to 3 months of antihypertensive medication was studied in 10 patients (39-56 years old) with essential hypertension. We used computerized microdensitometry on fundus photographs, a technique allowing for objective and simultaneous measures of the caliber of blood columns and the width and intensity of their central 'light reflex'. A moderate lowering of diastolic and systolic blood pressures (P less than 0.001) resulted in a significant reduction in the intensity of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Other studies are inconclusive on this question; sympathectomy was reported to improve focal constriction of retinal arterioles [61], presumably as a result of reduced blood pressure because retinal arterioles do not receive a sympathetic innervation, whereas Dollery et al [62] reported that treatment of hypertension did not significantly alter vessel diameter. Brinchmann-Hansen et al [20] reported that moderate blood pressure lowering was associated with a reduction of reflection from retinal vessels but that there were nonsignificant changes in the light reflex and vessel width. In a population-based study, Klein et al [4] reported that retinopathy and arteriolar narrowing were less common in treated compared with untreated hypertensive patients, whereas Dahlof et al [63] reported that blood pressure lowering with enalapril but not hydrochlorothiazide caused regression of arteriolar narrowing and arteriovenous crossing abnormalities in 28 previously untreated men with mild to moderate essential hypertension.…”
Section: Treatment and The Retinal Microvasculature Treatment And Thementioning
confidence: 96%
See 1 more Smart Citation
“…Other studies are inconclusive on this question; sympathectomy was reported to improve focal constriction of retinal arterioles [61], presumably as a result of reduced blood pressure because retinal arterioles do not receive a sympathetic innervation, whereas Dollery et al [62] reported that treatment of hypertension did not significantly alter vessel diameter. Brinchmann-Hansen et al [20] reported that moderate blood pressure lowering was associated with a reduction of reflection from retinal vessels but that there were nonsignificant changes in the light reflex and vessel width. In a population-based study, Klein et al [4] reported that retinopathy and arteriolar narrowing were less common in treated compared with untreated hypertensive patients, whereas Dahlof et al [63] reported that blood pressure lowering with enalapril but not hydrochlorothiazide caused regression of arteriolar narrowing and arteriovenous crossing abnormalities in 28 previously untreated men with mild to moderate essential hypertension.…”
Section: Treatment and The Retinal Microvasculature Treatment And Thementioning
confidence: 96%
“…A number of computer-assisted methods have been described to assist in the quantitative analysis of the retinal microvasculature based on digitized photographic negatives or directly acquired digital images [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. These are generally superior to manual methods and further improvement in accuracy and precision may be achieved by gating image acquisition to the electrocardiogram to ensure that image capture occurs at the same point in the cardiac cycle [34,35].…”
Section: Quantitative Measures Of the Retinal Microcirculation And Camentioning
confidence: 98%
“…Moreover, most methods fail to consider the central light reflex of blood vessels, resulting in large measurement errors. The central light reflex, which is shown in Figure 1, is generated from a rough reflecting surface and the intravascular erythrocytes, 16 and appears to be associated with diseases like hypertension and arteriosclerosis. 17,18 Inspired by above studies and existing problems, we present an improved methodology for automatic vessel width measurement.…”
Section: Introductionmentioning
confidence: 99%